2015
DOI: 10.1115/1.4029101
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Investigation on Tip Flow Field and Rotating Stall in Counter-Rotating Axial Compressor

Abstract: Contra-rotating axial compressor/fan (CRAC) is a promising technology to meet the future goals aircraft industry. Massive time accurate simulations are performed to investigate rotating stall in CRAC containing two counter-rotating rotors. Particularly, the back pressure increasing with a very small step to avoid missing flow field transition from stability to instability. Due to the canceling of the stator, the instability of downstream rotor is more stronger. The present studies mostly focus on the downstrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 5 publications
1
23
0
Order By: Relevance
“…They found that the first stall stage of counter-rotating compressor varies with the tip clearance size increases. An unsteady numerical investigation on tip flow and rotating stall in a CRAC by Gao et al 22 showed that a double-leakage flow 8 (the passage of tip clearance fluid through the neighboring tip clearance gap) plays an important role in the unsteadiness of CRAC's unsteady flow field. The frequency analysis also captured the transition of the second harmonic frequency, which can be used as stall inception signal.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the first stall stage of counter-rotating compressor varies with the tip clearance size increases. An unsteady numerical investigation on tip flow and rotating stall in a CRAC by Gao et al 22 showed that a double-leakage flow 8 (the passage of tip clearance fluid through the neighboring tip clearance gap) plays an important role in the unsteadiness of CRAC's unsteady flow field. The frequency analysis also captured the transition of the second harmonic frequency, which can be used as stall inception signal.…”
Section: Introductionmentioning
confidence: 99%
“…Tip leakage vortex plays a key role in stall inception, which has become a consensus. As found in many researches [15,[21][22][23], unsteady fluctuations are existed in the tip leakage flow field of most fans/compressors under the near-stall states, tip leakage vortex breaks under certain conditions, but disagreements are still appeared in mechanisms of unsteady flow phenomenon in tip regions. As demonstrated in numerical simulation of unsteady flow by Hu [24], weak unsteady character is stayed in the near-stall points of the low speed fan, which is basically consistent with the result obtained from the steady calculation.…”
Section: Effect Of Speed Ratio On Characteristics Of Tip Clearance Flmentioning
confidence: 95%
“…For example, a circumferential groove with its leading edge positioned at 20% tip axial chord length downstream of the blade leading edge is named G2. Previous research on this compressor has indicated that the flow fields in the tip region of R2 are responsible for the spike-type flow instability of the CRAC [35,37,38]. Therefore, different circumferential single grooves over the blade tip of R2 were numerically investigated in the current paper.…”
Section: Compressor Geometry and Ct Designmentioning
confidence: 99%
“…Endeavors to gain further insights into the flow physics in CRAC have been conducted on the important factors, including axial spacing between two rotors, unsteady effects, inlet distortion, etc. [30][31][32][33][34][35][36][37][38]. Compared with a conventional compressor stage, it was found that there are many new characteristics and unique flow phenomena in CRAC.…”
Section: Introductionmentioning
confidence: 99%